A review on environmental applications of chitosan biopolymeric hydrogel based composites - Nangia, Sakshi; Warkar, Sudhir; Katyal, Deeksha (Journal of macromolecular science. Part A, Pure and applied chemistry, 2018)
Chitosan (CS) is being used for fabrication of low cost, biocompatible materials that have applicability in fields such as agriculture, biotechnology and environment. In Environmental research, one of the applications of CS based hydrogel composites are in form of biosorbents for eviction of toxic dyes, heavy metals and nutrients from effluent streams. The adsorption potential could be attributed to the reactive functional groups existing on the surface of CS. CS based materials can also be employed for oil/water separation, as a fertilizer carrier, in Microbial fuel cells as Electrolyte membrane and as Electrochemical/Biosensors for detecting and analyzing few environmental pollutants such as pesticides. The earlier review papers on the subject matter have concentrated mainly on dye and heavy metal removal without giving details of its utility in the field of electrochemistry and agriculture. Though the biopolymer holds numerous applications, it has not been discussed extensively. Thus, an attempt has been made to elucidate the current and potential applications of CS hydrogels and composites based on the efficacy it has shown in areas of removal of organic and inorganic contaminants such as dyes, heavy metals and nutrients, in agriculture, oil and water separation, Microbial Fuel cells and Electrochemical/Biosensors. HIGHLIGHTS Chitosan based hydrogel composites could be extensively used in the field of Environment Technology. The composites act as effective biosorbents for dye, heavy metal and nutrient removal because of the functional groups present on Chitosan's surface. These can also be effectively used for oil/water separation and also as a fertilizer/pesticide carrier for their slow release. Chitosan based electrolytes can become a promising ecofriendly substitute for synthetic polymers in fuel cells. These biopolymers have also been researched upon as electrochemical/biosensors in recent years for detecting environmental pollutants.